Giardiasis in Childhood: Absorption Tests and Biochemistry, Histochemistry, Light, and Electron Microscopy of Jejunal Mucosa. Issue 242 (August 1970) - Barbieri, D.; de Brito, T.; Hoshino, S.; Nascimento F, O. B.; Campos, J. V̇. Martins; Quarentei, G.; Marcondes, E.
Abstract : Eleven symptom-free children with infestation by Giardia lamblia but without other diseases were studied by absorption tests and jejunal biopsy. Lipiodol and d -xylose tests showed a mild degree of malabsorption. Light microscopy showed no tissue invasion in the jejunal mucosa. The number and appearance of the villi were normal or almost normal, but the lamina propria was usually infiltrated by inflammatory cells. Electron microscopy showed an increased mucoid coat of the epithelial cells, branching and gaps in the microvilli, an increased number of cytoplasmic dense bodies, and intercellular spaces infiltrated with lamina propria inflammatory cells. Biochemical and histochemical studies of acid phosphatases, alkaline phosphatases, and succinic dehydrogenase showed no differences in enzyme activity of the jejunal epithelia before and after treatment. It is suggested that the malabsorption which occurs in giardiasis depends on several factors, such as blockade of the mucosa by the parasite, nutritional competition between host and parasite, and changes in the jejunal mucosa due to the presence of protozoa.